Fermi surface and effect of high magnetic fields on the metal–semimetal Peierls-like transition of (TSeT)2Cl: Электронная структура и Ферми поверхность - Laukhin, Vladimir; Audouard, Alain; Vignolles, David; Drigo, Loïc; Alemany, Pere; Canadell, Enric (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Resistance measurements in pulsed magnetic fields up to 55 T as well as a first-principles DFT calculation of the Fermi surface for the organic metal (TSeT)2Cl have been performed to investigate its metal–semimetal phase transition. The results obtained are in line with the imperfect nesting that can be inferred from both the observed metallic behavior of the resistivity at low temperature and the previously reported Shubnikov–de Haas oscillations due to small carrier pockets. The DFT study points out the possibility that the LUMO bands of the TSeT donor may interact with the HOMO ones and modify the shape of the Fermi surface under pressure.